ANALISIS HUBUNGAN PANJANG BERAT DAN NISBAH KELAMIN UDANG KARANG (Panulirus spp) DI KEPULAUAN SPERMONDE SULAWESI SELATAN - Hasrun Abdullah; Kasmawati Saleh (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2018)
The Spermonde Island consists of 120 is one of the island's territory the spread of coral reefs is quite extensive, which is located in the territorial waters of Makassar Strait is a wealth of biological resources that are potential good flora as well as fauna among them are Spiny Lobster (Panulirus spp). The purpose of this research is to know the kinds of Spiny Lobster, length-weight relationship and the sex ratio in the spermonde Island. To achieve these goals then performed the measurement of biological parameters, namely the measurement of length, weight, and sex ratio determination. The method to be used is the measurement of the length of the carapace with uses measurent board, heavy with weights, and to sex by looking at the characteristics on the abdomen. Observations made on the island was the location of a 6 catching Spiny Lobster by dividing three (3) Zones based on the distance from the coast and the population.Was found that there were three types of Spiny Lobster namely spiny lobster pearls (P. Ornatus) as 334 individual lobster or 39,06 %, Spiny Lobster bamboo (P. versicolor) as many as 312 individual lobster or 36,49 %, and Spiny Lobster batik (P. Longipes) as 209 individual lobster or 24,44 % .The sex ratio of spiny lobster of spiny lobster batik (P. longipes) is 0,51:0,49, or (1:1) , Spiny Lobster pearls (P.ornatus) is 0,51: 0,49 or (1:1) and Spiny Lobster bamboo (P. Versicolor) is 0,63: 0,37 or (2:1). Pattern growth Spiny Lobster bamboo is allometrik negative, and the pattern growth Spiny Lobster pearls and Spiny Lobster batik is allometrik major .